Construction of New Ion Selective Electrodes for Determination Chloramphenicol Sodium Succinate and Their Application in Pharmaceutical Samples - Al-Saidi, Khaleda H; Aziz, Weaam R (Al-Nahrain Journal of Science, 2012)
A liquid membrane electrodes for the determination chloramphenicol sodium succinate were constructed based on chloramphenicol palmitate and sodium tetraphenyl borate, and with four plasticizers, Di-butyl phthalate (DBPH); Di-butyl phosphate (DBP); Di-octyl phthalate (DOP); Tri-butyl phosphate (TBP); in PVC matrix. These electrodes give sub- Nernstian slopes (53.98, 51.45, 49.66 and 48.98 mV/decade) and linear ranges from (1x10-4-1x10-1, 5x10-4-1x10-1, 1x10-4-1x10-1, 5x10-4-1x10-1 M) respectively. The best electrode was based on DBPH plasticizer which gave a slope 53.98 mV/decade, correlation coefficient 0.9999, detection limit of 5 x 10-5 M, lifetime 50 day displayed good stability and reproducibility and used to determine the Chloramphenicol sodium succinate in pharmaceutical samples. The measurement interferences in the presence of K+, Na+, Fe+3, Al+3, Cu+2, Mn+2, sucrose, Gelatine and Chloramphenicol palmitate were studied using the separated and mixed methods for selectivity coefficient determination. The pH and life time of the electrodes were also studied. The results were compared statistically with UV-spectrophotometeric technique by using F-test.Keywords: Chloramphenicol sodium succinate selective electrodes, sodium tetraphenylborate, Chloramphenicol palmitate.